Diagnosis dan Tata Laksana Varises Tungkai - Setiawan, Kayan; Hengky, Tan (PT Kalbe Farma Tbk., 2024)
Varicose veins are characterized by the elongation, widening, and twisting of the venous system, accompanied by impaired blood circulation. It usually occurs in lower extremities, with a prevalence of 10%-30%. It affects mainly women, and the prevalence rate increases with age. The CEAP (Clinical, Etiological, Anatomical, and Pathophysiological) classification allows for a more precise diagnosis and provides better results. Treatment includes conservative therapy and intervention. With appropriate management, postoperative care, and rehabilitation, the prognosis of varicose veins is generally good.